The Estimation of genetic divergence and determining selection criteria in sesame (Sesamum indicum) - KUMARI, MANISHA; CHOUDHARY, B R; BHARDWAJ, RAHUL (The Indian Journal of Agricultural Sciences, 2023)
Twenty eight mutant lines of sesame were evaluated in randomized block design at Agricultural Research Station, Mandor, Jodhpur, Rajasthan, during kharif, 2018. ANOVA stated the existence of significant difference for all the characters studied. The percentage contribution towards genetic divergence was found highest for test weight followed by number of capsules/plant and seed yield/plant.Character association study indicated that simultaneous selection for the traits like harvest index, oil content, capsule length and number of capsules and direct selection for protein content, capsules/plant, length of capsule, days to maturity and harvest index will  be advantageous for aiding yield improvement. Out of ten independent characters studied in path coefficient three traits, viz. number of capsules/plant, capsule length and harvest index expressed maximum directas well as indirect contributions through other characters on seed yield. Hence, these characters may be considered as important quantitative traits in sesame improvementprogramme and direct selection for these traits will be useful.